A novel test device and quantitative colorimetric method for the detection of human chorionic gonadotropin (hCG) based on Au@Zn–salen MOF for POCT applications. Issue 17 (14th April 2023) - Mohamed, Reda M.; El-Sheikh, Said M.; Kadi, Mohammad W.; Labib, Ammar A.; Sheta, Sheta M.
Abstract : The human chorionic gonadotropin (hCG) hormone is a biomarker that can predict tumors and early pregnancy; however, it is challenging to develop sensitive qualitative-quantitative procedures that are also effective, inventive, and unique. Abstract : The human chorionic gonadotropin (hCG) hormone is a biomarker that can predict tumors and early pregnancy; however, it is challenging to develop sensitive qualitative-quantitative procedures that are also effective, inventive, and unique. In this study, we used a novel easy in situ reaction of an organic nano-linker with Zn(NO3 )2 ·6H2 O and HAuCl4 ·3H2 O to produce a gold–zinc–salen metal–organic framework composite known as Au–Zn–Sln-MOF. A wide variety of micro-analytical instruments and spectroscopic techniques were used in order to characterize the newly synthesized Au–Zn–Sln-MOF composite. Disclosure is provided for a novel swab test instrument and a straightforward colorimetric approach for detecting hCG hormone based on an Au–Zn–Sln-MOF composite. Both of these methods are easy. In order to validate a natural enzyme-free immunoassay, an Au–Zn–Sln-MOF composite was utilized in the role of an enzyme; a woman can use this gadget to determine whether or not she is pregnant in the early stages of the pregnancy or whether or not her hCG levels are excessively high, which is a symptom that she may have a tumor. This cotton swab test device is compatible with testing of various biological fluids, such as serum, plasma, or urine, and it can be easily transferred to the market to commercialize it as a costless kit, which will be 20–30% cheaper than what is available on the market. Additionally, it can be used easily at home and for near-patient testing (applications of point-of-care testing (POCT)).